Fostering Religious Moderation in Children: Parental Approaches in the Era of Industry 4.0 - Taubah, Mufatihatut; Mailasari, Dewi Ulya; Isroani, Farida; Fais, Noor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Religious moderation is crucial for fostering harmony in diverse societies but faces challenges such as extremism, social polarization, and discrimination against minorities. In Indonesia, efforts to strengthen religious moderation include interfaith dialogue and community programs. Early childhood education plays a vital role in instilling moderate values, helping prevent radicalization, and promoting tolerance. This study explores parental strategies for fostering religious moderation among children in the Industry 4.0 era. This research is field research, namely by conducting data mining on subjects or data sources in the social setting where the research was conducted. This research approach uses a case study on efforts to strengthen the foundation of children's religious moderation character in families in the Industry 4.0 era. Findings indicate that religious education, parental role modeling, and community participation significantly shape children's moderate attitudes. Strengthening religious moderation requires a balanced approach integrating education, guidance, and social engagement to nurture a generation that respects diversity and coexists peacefully in a pluralistic society.